2014
DOI: 10.1016/j.neuro.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicology and development: Human, environmental and social impacts

Abstract: The 12th International symposium of the Scientific Committee on Neurotoxicology and Psychophysiology, International Commission on Occupational Health was held in Cape Town, South Africa on March 24 – 27, 2013. Reflecting the meeting aiming to build greater focus on challenges facing working populations and communities in developing countries, the Symposium theme was Neurotoxicology and Development: Human, Environmental and Social Impacts. A total of 23 countries were represented with strong participation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It has been suggested that alcohol may have an effect by inhibiting the N-methyl-D-aspartate receptor (NMDA) receptor and activating GABA receptors, and can promote apoptosis by affecting the activities of Na + /K + -ATP enzymes, the adenosine acid cyclization enzyme, and opening of Ca 2+ channels. Others have suggested that the pharmacological and toxicological mechanisms of alcohol may work through ceramide (4,5). As an important cellular signal transduction carrier, ceramide is involved in a variety of cellular signal transduction pathways, and has multiple cellular physiological functions, including regulation of the cell cycle, cell differentiation and proliferation, regulation of apoptosis, and being involved in stress, immunity and inflammation (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that alcohol may have an effect by inhibiting the N-methyl-D-aspartate receptor (NMDA) receptor and activating GABA receptors, and can promote apoptosis by affecting the activities of Na + /K + -ATP enzymes, the adenosine acid cyclization enzyme, and opening of Ca 2+ channels. Others have suggested that the pharmacological and toxicological mechanisms of alcohol may work through ceramide (4,5). As an important cellular signal transduction carrier, ceramide is involved in a variety of cellular signal transduction pathways, and has multiple cellular physiological functions, including regulation of the cell cycle, cell differentiation and proliferation, regulation of apoptosis, and being involved in stress, immunity and inflammation (6,7).…”
Section: Introductionmentioning
confidence: 99%